The conquering tide : war in the Pacific Islands, 1942-1944 - Toll, Ian W. (W. W. Norton & Company, 2015)
"This ... history encompasses the heart of the Pacific War--the period between mid-1942 and mid-1944--when parallel Allied counteroffensives north and south of the equator washed over Japan's far-flung island empire like a 'conquering tide,' concluding with Japan's irreversible strategic defeat in the Marianas. It was the largest, bloodiest, most costly, most technically innovative and logistically complicated amphibious war in history, and it fostered bitter interservice rivalries, leaving wounds that even victory could not heal"--Dust jacket flap.